PELATIHAN PENELITIAN TINDAKAN KELAS (PTK) BAGI PENGAJAR DAN CALON PENGAJAR DI SITUBONDO - Nine Febrie Novitasari (Relawan Jurnal Indonesia, 2017)
An initial observation was made to see how many students at UNARS who have been teaching at any formal or informal institution. The result of the observation showed that some students of UNARS had been working as either an in-service teacher or a pre-service teacher. However, since they were not majoring in teaching program, they were well not equipped with enough teaching skills. This then led to their failure in identifying the problems they had when teaching. Concerning this fact, a one-day training on Classroom Action (CAR) research was held for these in-service and pre-service teachers. The most fundamental reason of holding the training is these teachers’ insensitivy in identifying problems occuring in their classes. Further, the problems often lasted long because the solutions given were less precise and sometimes there were not any solutions given. Therefore, the training aimed at equipping the in-service and pre-service teachers with enough knowledge and understanding about Classroom Action Research (its conceptual theory, application, and report format). To improve the quality of students’ learning process, these pre-service and in-service teachers were given Classroom Action research (CAR) training. This training included mentoring on how to recognize and analyze problems that occur in the classroom, providing solutions, and how to write the proposal and report format of Classroom Action Research. The expected outcomes of this training include the compulsory extent of scientific publication in national journals.